(untitled) (Research, Society and Development, 2026)
The objective of this study is to report a clinical case of hemorrhage in the floor of the mouth following dental implant placement, as well as to highlight the management of such hemorrhagic events. Methodology: this is a retrospective, descriptive, observational study based on the analysis of medical records, imaging examinations, and photographic documentation, with patient authorization obtained through an informed consent form. Results: A hypertensive female patient was referred to the Hospital Universitário do Oeste do Paraná for emergency care after hemostatic control measures with tranexamic acid were unsuccessful due to active bleeding following dental implant placement in the left mandibular canine region. Computed tomography revealed a hypodense mass in the interforaminal region. During the surgical procedure under general anesthesia, due to involvement of an accessory lingual foramen, implant removal, vessel cauterization, and suturing were performed. Management of floor-of-the-mouth hemorrhage must be immediate in order to prevent airway compromise. Conclusion: Dental implant surgeries are safe and effective procedures for the rehabilitation of edentulous patients. However, intraoperative and postoperative complications may occur. A thorough medical history, individualized case assessment for systemically compromised patients, and complementary examinations prior to surgical intervention are essential. Hemorrhage is generally caused by vascular injury associated with perforation of the lingual cortical plate in the anterior mandibular region and damage to the sublingual and submental arteries, which are more susceptible due to possible local anatomical variations.